Examination of “Disparity Correction” in the Field of Education: Influence of the Dowa Policy Council Recommendation and the Law on Special Measures for Dowa Projects - ITAYAMA, Katsuki (THE JAPANESE JOURNAL OF EDUCATIONAL RESEARCH, 2023)
The aim of this paper is to critically examine the “disparity correction” which has been implemented in the field of education, based on the Dowa Policy Council Recommendation and the Law on Special Measures for Dowa Projects, in order to clarify the conflicts created and the historical reasons. First of all, the paper confirms that the Dowa Policy Council Recommendation made it a central issue to reduce “disparity correction,” and that it reflected the intentions of Kitahara Taisaku and Asada Zennosuke. Secondly, it shows that three propositions have affinity with the Dowa Policy Council Recommendation. These three propositions were intended to support the route of “disparity correction” from the standpoint of the Buraku Liberation League. The paper then shows that “disparity correction” had become a tactical goal for those who aimed for Buraku liberation.  Thirdly, the paper finds that the Dowa Policy Council Recommendation had planned to intensively distribute educational resources to Dowa districts (redistribution of resources) for the purpose of reducing disparity. Along with this, it also indicates two issues that would lead to the "correction of disparities" (the emergence of overcoming "low academic achievement" and special countermeasures in education in the Dowa districts). Fourth, the paper points out that these two issues have resulted in reduced engagement with the formation of “subjects of liberation.” In association with “disparity correction” becoming a tactical goal for Buraku liberation, overcoming "low academic achievement" was adopted, and Dowa education shifted to focus on special countermeasures in education in the Dowa districts. The paper clarifies that these two events demonstrate a new issue which created and reinforced reduced engagement with the formation of “subjects of liberation” in regard to Dowa education.